MEDIATING ROLE OF FINANCIAL PERFORMANCE IN OWNERSHIP STRUCTURE'S IMPACT ON FIRM VALUE OF LISTED COMPANIES IN THE LQ45 INDEX OF THE INDONESIA STOCK EXCHANGE - Hestu Nugroho Warasto; Janudin Janudin (International Journal Multidisciplinary Science, 2024)
This study aims to analyze the effect of ownership structure on firm value with financial performance as a mediating variable in companies listed in the LQ45 index of the Indonesia Stock Exchange during the 2020-2024 period. The independent variables consist of institutional ownership and managerial ownership, while the mediating variable is financial performance measured using Return on Assets (ROA). Firm value, as the dependent variable, is measured using Price to Book Value (PBV). Using multiple linear regression methods and the Sobel test, the study found that managerial ownership significantly influences firm value, whereas institutional ownership does not show a significant impact. Additionally, financial performance does not act as a mediator in the relationship between ownership structure and firm value. The findings of this study provide important implications for corporate governance in Indonesia, particularly in managing ownership structures to enhance financial performance and maximize firm value.